Rôle des conditions géographiques sur l'organisation spatiale des réseaux de défense de la Grande Guerre. Application à la Champagne (région de Reims) - Alain Devos; Pierre Taborelli; Mylène Dodici; Laurent Chalumeau; Jérôme Buridant; Nicolas Bollot; Anne Combaud; Yves Desfossés (Physio-Géo)
The control of geographical and geomorphological conditions on the spatial organization of the First World War defenses of networks is analyzed from the Reims area, on the western front. It is performed in GIS, from battle maps crossword Shooting canvas groups to available databases (DEM, geology, hydrography). The trench systems exhibit a triple nested organization in defense of curtains and structured lines and hoses whose logic not only meets geomorphological criteria multiscale (role of cuesta fronts, the reverse slopes, embankments communication channels) but also military (shooting crests worn artillery). This approach reflecting the importance of knowledge and the exploitation of ground in the war of position also measure the environmental impact of the Great War (disturbance of land, soil pollution, underground cavities hazards).